The Effect of Foot Exercises on Blood Sugar Control Through Education of Families With Diabetes Mellitus in The Medical Surgery Room of Banten Province Hospital - Imas Sartika; Sonia Aprilia; Umi Kulsum (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Diabetes is a chronic metabolic disorder characterized by increased blood glucose (or blood sugar) levels, which over time causes serious damage to the heart, blood vessels, eyes, kidneys and nerves. Type 2 diabetes mellitus is the most common diabetes, which generally occurs in adults, which occurs when the body becomes resistant to insulin or does not produce enough insulin. Treatment that can be done for diabetes mellitus is pharmacological therapy and non-pharmacological therapy. One of the non-pharmacological management of DM is doing foot exercises. According to Riskesdas in 2018, Banten was the province with the highest increase in DM from 2013 to 2018. The prevalence of DM in Banten province was 2.43%. The aim of this activity is to provide knowledge to families and patients about foot exercises for diabetes mellitus sufferers. The activity was carried out at the Banten Regional General Hospital in the medical-surgical room, which was attended by the patient and the patient's family. The method of activity carried out was providing material on the influence of foot exercises on blood sugar control through educating families with diabetes mellitus, demonstrating foot exercise activities for DM sufferers, after that a question and answer session was held, participants were active in asking and answering. The activity took place for one day in June 2024. The results of this activity are that families of patients suffering from Diabetes Mellitus understand that blood sugar can be controlled through foot exercises, families can do foot exercise demonstrations independently and families also understand how to prevent Diabetes Mellitus from occurring. by other family members